Upaya Meningkatkan Kemampuan Pemecahan Masalah Matematika Melalui Pendekatan Pembelajaran Problem Solving Pada Siswa Kelas X SMA Negeri 8 Pandeglang - Mumun Mumun (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2019)
Based on the observation, the problem solving abilities in class X is low. The average achievement score is 19.13 while the ideal average score that must be achieved is 30. Based on this, actions and efforts are needed so that students' problem solving abilities increase. This research method is a classroom action research with 3 cycles. The results of the study show that with the application of problem solving learning methods, problem solving skills of high school students in class X have been raised to 8 levels of improvement